2016
DOI: 10.1021/acs.nanolett.6b01152
|View full text |Cite
|
Sign up to set email alerts
|

Patterning Superatom Dopants on Transition Metal Dichalcogenides

Abstract: This study describes a new and simple approach to dope two-dimensional transition metal dichalcogenides (TMDCs) using the superatom Co6Se8(PEt3)6 as the electron dopant. Semiconducting TMDCs are wired into field-effect transistor devices and then immersed into a solution of these superatoms. The degree of doping is determined by the concentration of the superatoms in solution and by the length of time the films are immersed in the dopant solution. Using this chemical approach, we are able to turn mono- and few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 29 publications
(56 reference statements)
1
47
0
Order By: Relevance
“…Remarkably, covering BP by Cs 2 CO 3 film with thickness of >10 nm or MoO 3 film (even particles, <1 nm) will induce a change in types of majority charge carriers. Based on a similar idea, Yu et al recently achieved unipolar p‐ and n‐type WSe 2 using superatom Co 6 Se 8 as electron dopants . It was noted that this change between two unipolar conductions were only observed in thin (here bilayer) WSe 2 flakes, demonstrating that the surface‐decoration way only affects the top‐most layer/layers of 2DLSMs.…”
Section: Tuning the Device Performancementioning
confidence: 99%
“…Remarkably, covering BP by Cs 2 CO 3 film with thickness of >10 nm or MoO 3 film (even particles, <1 nm) will induce a change in types of majority charge carriers. Based on a similar idea, Yu et al recently achieved unipolar p‐ and n‐type WSe 2 using superatom Co 6 Se 8 as electron dopants . It was noted that this change between two unipolar conductions were only observed in thin (here bilayer) WSe 2 flakes, demonstrating that the surface‐decoration way only affects the top‐most layer/layers of 2DLSMs.…”
Section: Tuning the Device Performancementioning
confidence: 99%
“…This can be improved by further increasing the WSe 2 base-region thickness to above three layers. [36,37] We are confident that using an electron-rich octahedral superatom as an electron dopant for MoS 2 [38] and choosing a Pd metal with a high work function for WSe 2 to reduce the Schottky barrier height [39] are two effective ways to further improve the V2D-BJT performance. With a threelayer WSe 2 base region (Figure 4f), I C first linearly increases with V CE and then nearly becomes unaffected by changing V CE (e.g., V CE > 2 V); instead, it is almost entirely controlled by V BE .…”
Section: Resultsmentioning
confidence: 99%
“…However, it decreased for n-type doped MoS 2 with NADH. Yu et al (2016) reported the synthesis of superatom-doped MoS 2 and WSe 2 via a chemical doping method. The superatom, Co 6 Se 8 (PEt 3 ) 6 , is an electron-rich octahedral dopant as shown in Fig.…”
Section: Chemical Dopingmentioning
confidence: 99%